Sosialisasi Menumbuhkan Jiwa Entreprenuership di Usia Remaja Pada Era Digital Bagi Santri Yayasan Pondok Pesantren Tahfidz Quran Lailatul Qodar - Lestari, Indawati; Dalimunthe, Hasbiana (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Community service is one of the tertiary institutions' programs for the community whose goal is to develop science and technology as an effort to support and improve people's welfare. In this program to foster an entrepreneurial spirit, the team conducted socialization regarding entrepreneurship and the application of digital marketing in the digital era in carrying out business activities, moreover the Tahfidz Quran Laitul Qodar Islamic Boarding School Foundation has a business of cultivating oyster mushrooms and goat farming, therefore through the Community Service program carried out by the Medan Area University Lecturer, it is hoped that it will be able to foster an entrepreneurial spirit not only for students of the Tahfidz Quran Laitul Qodar Islamic Boarding School but for other young entrepreneurs and be able to take advantage of technology that is increasingly developing in the current digital era in managing their business. This activity is divided into four stages including observation, outreach, training and evaluation. The results of this dedication have achieved success by increasing insight, skills and interest in entrepreneurship by fostering an entrepreneurial spirit and implementing digital marketing in the Foundation's business activities, one of which is the cultivation of oyster mushrooms.